SISTEM INFORMASI GEOGRAFIS VISUALISASI PERSEBARAN TENAGA KESEHATAN DI KOTA SEMARANG BERBASIS WEB - Nadila Dwi Farida Rahmatin (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Equitable distribution of health facilities and services is crucial to ensure the success of health aspects in a region. Integrated and well-directed health development requires the establishment of healthcare services that are fair, equitable, safe, high-quality, and affordable to fulfill the rights and health needs of the community. In the city of Semarang, relevant, accurate, and easily accessible data or information is essential to support the success of health aspects. This is to make effective decisions and actions regarding the issue of evenly distributed health facilities and services by the government or stakeholders. This research develops a web-based Geographic Information System (GIS) to understand and analyze the distribution of healthcare professionals in each district in the city of Semarang. The study focuses on the distribution of doctors, nurses, pharmacists, nutritionists, environmental health professionals, public health professionals, and biomedical professionals in the years 2021/2022. The data used include spatial and non-spatial data, with non-spatial data sourced from the official website of the Central Statistics Agency (BPS) of Semarang city. The website is created interactively and is easily accessible using HTML, CSS, and Bootstrap programming languages. The existence of this website contributes to planning or decision-making regarding health policies and the improvement of healthcare service availability. Furthermore, it aids the public in viewing an interactive map of the distribution of healthcare professionals and facilities accessible at the site https://sig5dinformatika.com/21670045/.